2016
DOI: 10.1128/jcm.01066-16
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Range PCR Coupled with Electrospray Ionization Time of Flight Mass Spectrometry for Detection of Bacteremia and Fungemia in Patients with Neutropenic Fever

Abstract: Infection is an important complication in patients with hematologic malignancies or solid tumors undergoing intensive cytotoxic chemotherapy. In only 20 to 30% of the febrile neutropenic episodes, an infectious agent is detected by conventional cultures. In this prospective study, the performance of broad-range PCR coupled with electrospray ionization time of flight mass spectrometry (PCR/ESI-MS) technology was compared to conventional blood cultures (BC) in a consecutive series of samples from high-risk hemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…We found only one study that investigated polymicrobial specimens. Here, the Iridica platform identified only one causative organism in four out of nine cases of blood culture-positive polymicrobial infection (94).…”
Section: Modern Nucleic Acid Amplification Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…We found only one study that investigated polymicrobial specimens. Here, the Iridica platform identified only one causative organism in four out of nine cases of blood culture-positive polymicrobial infection (94).…”
Section: Modern Nucleic Acid Amplification Technologiesmentioning
confidence: 99%
“…Iridica has been evaluated in a limited number of clinical studies across patients with suspected sepsis, systematic inflammatory respiratory syndrome (SIRS), and febrile neutropenia (54,(92)(93)(94)(95). Interestingly, significant differences in sensitivity have been reported across ICU and emergency room (ER) patients (P ϭ 0.005), with higher sensitivity being seen for ICU patients (92).…”
Section: Modern Nucleic Acid Amplification Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…20,118 In a meta-analysis of 54 studies, pooled sensitivity and specificity for the diagnosis of IC (mainly candidemia) of PCR methods were 95 and 92%, respectively. 144 However, performance of both in-house and commercial PCR varied markedly across studies, [144][145][146][147][148] and no test has been validated for the diagnosis of candidemia through dedicated, large, multicenter experiences. In view of these considerations, PCR-based tests, although promising, have still to be included in diagnostic guidelines and standardized definitions of candidemia.…”
Section: Rapid Tests Based On Polymerase Chain Reactionmentioning
confidence: 99%
“…Seven previous studies of PCR/ESI-MS on 5-ml whole-blood samples (9, 10, 14-18) reported BC positivity rates of 5.4 to 34% and PCR/ESI-MS positivity rates of 10.6 to 37% (19). Higher rates of PCR/ESI-MS-positive results (versus BC) were seen in 5 of those studies (9,10,14,16,18), and more BC-positive results (versus PCR/ESI-MS) were seen in 2 studies (15,17). In the largest previous study (n ϭ 616), by Vincent et al (10), BC was positive in 11% and PCR/ESI-MS was positive in 37% of the cases.…”
Section: Discussionmentioning
confidence: 99%